Dynamic process modelling using Petri nets with applications to nuclear power plant emergency management. (18th December 2008) - Tavana, Madjid
Complex information systems are difficult to model and expensive to build. Numerous process modelling methodologies, such as action workflow, data flow diagrams, decision trees, entity relationship diagrams, process maps, role activity diagrams and role interaction nets, have been developed to provide high level abstraction of a system. Despite their huge popularity, these methodologies cannot depict and verify the dynamic requirements of a system. In this study, we use Petri Nets (PNs) for dynamic process modelling of the emergency management system at a nuclear power plant. Decision trees used prior to PNs at the plant were inadequate for modelling complex emergency processes exhibiting sequential execution, conflict, concurrency, synchronisation, merging, confusion, or prioritisation. PNs with their graphical and precise nature and their firm mathematical foundation are especially useful in reducing the number of false evacuations at the plant.